Pension Fund Investment Strategy: A Quantitative Study for the Asset Allocation in UK Defined Benefit Pension Schemes - He, Pei (2008)
In recent years, the so-called pension crisis in the UK has drawn large attention in both business and academic world (Booth et al. 2004; Billings et al. 2006; O'Brien and Woods, 2006). In addition, it has become an important public issue since pension plays a central part in social welfare (Ombudsman, 2006). One important element that characterises this crisis is the large scale of the deficits reported by major listed companies in respect of their defined benefit pension schemes. Such deficits are partly due to the falling equity market and partly because of the overall increasing longevity of pensioners. More importantly, the strategic pension asset allocation has been seen as critical determinant of pension fund investment performance (Myners, 2001). However, the pension asset allocation is an under-resourced activity and struck by lack of clear objective and guidance (Myners, 2001). Therefore, the empirical analysis of how do pension fund trustees make their asset allocation decision in practice is of value to the pension fund profession, pension accountants and legislation regulators and the public at large.